Implementation of Maritime Transportation Service Policy in Riau Province (Study on the Ro-Ro Ship Dumai – Tanjung Kapal Pulau Rupat) - Manik, Christina Egluera Br; Simanjuntak, Harapan Tua Ricky Freddy (QISTINA: Jurnal Multidisiplin Indonesia, 2024)
Sea transportation is a mobile bridge that acts as a link between areas separated by water. Rupat Island is an area surrounded by waters and designated as a National Tourism Strategic Area that can only be accessed using sea transportation. Sea transportation used to connect Rupat Island with Dumai City is the Ro-Ro (Roll On-Roll Off) ship. This research is motivated by various problems in the implementation of the Ro-Ro ship crossing service policy, including inappropriate vehicle spacing on the ship, exceeding load capacity, and deviation from the predetermined operational schedule. The purpose of this study is to determine and analyze the implementation of sea transportation service policies and to identify obstacles in the implementation of sea transportation service policies in Dumai - Tanjung Kapal, Rupat Island. This research employs Warwick's theory (1979), which comprises three components: Political Leadership Commitment, Organizational Capability, Implementation Commitment, and Interest Group Support. The method used in this research is descriptive qualitative research, utilizing data collection techniques such as observation, interviews, and documentation. The implementation of the Dumai - Tanjung Kapal, Rupat Island Ro-Ro boat sea transportation service policy is overseen by the Riau Provincial Transportation Agency and managed by UPT Transportation Management Region I, UPT Pelabuhan Rupat District, and BPTD. However, third-party ship operators have not efficiently executed these policies, encountering various obstacles including stakeholders' lack of understanding of their roles and functions, insufficient budget for infrastructure development, and limited community response to service improvements. To optimize the implementation of Ro-Ro ship service policies in accordance with Minister of Transportation Regulation Number 115 of 2016 and Minister of Transportation Regulation Number 62 of 2019, these obstacles must be addressed to ensure service standards are met.